Cosmic blackout! - O'Ryan, Ray (O'Ryan, Ray. Galaxy Zack, 2017)
Zack loves everything about his new planet, Nebulon, until there is a complete cosmic blackout and he must try to function without his Indoor Robotic Assistant and hyperphone.